Effects of Relative Humidity on the Diurnal Variation of Raindrop Size Distribution in Southwest China - Sun, Jing; Wan, Rong; Zhou, Yue (Frontiers in Environmental Science, 2022)
This study examined the effects of relative humidity (RH) on the diurnal variation of raindrop size distribution (RSD) over valley topography (Zigui region) of China from 2019 to 2020 based on a two-dimensional video disdrometer (2DVD), auto-weather station (AWS) and ERA5. The RSD structure of daytime shows a triple peaks when the RH is lower than 60% and it shows a single peak in other RH conditions, for the RSD of nighttime, the RSD structure shows a single peak when the RH is greater than 60%, and the RSD shape shows a bimodal structure with RH ≤ 60%. Significant day-night difference was found in RSDs between short-duration precipitation Amount (SPA) and long-duration precipitation Amount (LPA) under the different RH conditions. The daytime RSDs of SPA showed broader distributions than the nighttime RSDs, whereas the nighttime RSDs of LPA exhibited the opposite to that of SPA. Higher ground RH modified the RSD shape through raindrop sorting, collision-coalescence and breakup resulting with the formation of large size raindrops. Under the effect of same RH, the melting and collision-coalescence of large raindrops in the daytime of SPA are obviously stronger than those of LPA. This difference may be related to the near-surface wind filed and the intensity of convection.